Individual differences and development in organizations - Pearn, Michael (b)
How can we maintain competitive advantage in a rapidly changing environment and at the same time create and sustain organisations in which people thrive both materially and psychologically? While organisations are facing the twin challenges of advancing technologies and increasing levels of competition, successfully developing and retaining the talents of all its members is key to organisational effectiveness. Individual Differences and Development in Organisations is a wide-ranging review of research, theoretical developments and current best practice for HR consultants, managers, academics
Includes references and index.
Keywords: Diversity in the workplace